Investigation on contamination of 16 kinds of mycotoxins in wine and risk assessment of aflatoxin B1 exposure - YANG Xueli, TIAN Jialei, WANG Meng, LUO Wentao, YANG Yalei, LI Fang (Zhongguo niangzao)
To investigate the pollution status of 16 mycotoxins in wine in Xinjiang, and to evaluate the exposure risk of aflatoxin B1 (AFB1) from wine in Xinjiang residents. A total of 85 wine samples were collected and 16 mycotoxins were detected by isotope dilution-liquid chromatography-tandem mass spectrometry (ID-UPLC-MS/MS). Combined with the dietary consumption survey data of Xinjiang residents, AFB1 exposure risk from wine sources in different gender and age groups was assessed using simple distribution method, and the health risk was characterized by margin of exposure (MOE) method and liver cancer risk quantitative method. The results showed that mycotoxins were detected in 35 out of 85 wine samples, the detection rate was 41.2%, and the detection rate of AFB1 was the highest (36.5%), with the average content ranging from 0.084 μg/kg to 0.324 μg/kg. The average exposure range of Xinjiang residents to AFB1 from wine was 0.005 0-0.009 5 ng/(kg bw·d). Margin of exposure assessment showed that the MOE value of the general population of Xinjiang residents was greater than 10 000 at the average exposure level, which did not need priority attention. The results of liver cancer risk assessment showed that the intake of AFB1 by Xinjiang residents accounted for 0.000 8%-0.001 6% of the overall incidence of liver cancer in Northwest China, and the contribution rate was relatively low. There were mycotoxins contamination in Xinjiang commercial wine, but the level of contamination was not high, and the health risk of dietary AFB1 through wine exposure among Xinjiang residents was low.